Pandiastolic antegrade flow in patient with severe right ventricle to pulmonary artery conduit stenosis: An interesting phenomenon - Neeraj Awasthy; Chintan Bhatt; Krishna Subramony Iyer (Wolters Kluwer Medknow Publications, 2016)
In a post operative tetralogy of fallot (TOF) physiology patient, abnormal right ventricular (RV) function remains the greatest matter of concern. Due to restrictive RV diastolic dysfunction, there is detectable antegrade diastolic flow in the pulmonary artery during atrial systole. We report a case of 21 year old male patient with total correction done in infancy using right ventricle to pulmonary artery conduit. He was relatively asymptomatic with a unique pattern of antegrade diastolic flow in both early and late diastolic phases (pan diastolic). This physiology was supportive and made him relatively asymptomatic. We discuss the physiology and clinical implication of the same.